Reinforced high-pressure flange composite material containing nano tungsten carbide and preparation method of reinforced high-pressure flange composite material
By adding nanotungsten carbide and a variety of synergistic substances to the duplex stainless steel flange, a multi-layer structural system and interface regulation network are formed, which solves the stress corrosion cracking problem of duplex stainless steel flange in high-temperature and high-pressure corrosive media, and significantly improves the corrosion resistance of the material.
Patent Information
- Application Number
- CN202510333322.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-20
AI Technical Summary
Duplex stainless steel flanges are prone to stress corrosion and cracking in high-temperature and high-pressure corrosive media environments, and the prior art is difficult to effectively solve this problem.
Using a high-pressure flange composite material containing nano-tungsten carbide reinforced, the shell-core-shell multi-layer structure system and multi-stage interface regulation network are formed by adding nano-WC, MoS2 nanosheets, CF1.1 micropowder, V2O5-B2O3 composite oxide, Ag-Y2O3 composite powder and G/ZrO2 nanocomposite materials to the duplex stainless steel matrix.
The stress corrosion cracking resistance and corrosion resistance of the material are significantly improved. The critical stress strength factor in the H2S and Cl-combined environment is increased by about 2.5 times within the temperature range of 350-550℃, and the stress corrosion cracking sensitivity is reduced by more than 80%.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flange composite materials, and in particular to a nano-tungsten carbide-reinforced high-pressure flange composite material and a preparation method thereof. Background Art
[0002] Flanges are key connecting components in industrial piping systems, pressure vessels and reaction devices, and they play important connecting and sealing functions, especially in the fields of petrochemicals, nuclear power, marine engineering, etc. With the development of industrial technology, the requirements for flange materials under high temperature, high pressure and corrosive media working conditions are increasing.
[0003] Duplex stainless steel is widely used in high-pressure flange manufacturing due to its excellent strength-toughness matching, good resistance to pitting and crevice corrosion, and relatively low cost. Typical duplex stainless steels such as SAF2205 (22Cr-5Ni-3Mo-0.17N) and SAF2507 (25Cr-7Ni-4Mo-0.28N) have a dual-phase structure of austenite and ferrite, combining the toughness of austenitic stainless steel and the high strength and chloride ion corrosion resistance of ferritic stainless steel. However, in high-temperature and high-pressure corrosive media environments, duplex stainless steel flange materials still face a series of serious technical challenges.
[0004] First, duplex stainless steel is prone to embrittlement in the temperature range of 250-550℃, which leads to the formation of chromium α' phase in the ferrite phase, making the material embrittled and seriously reducing the mechanical properties and safety of the flange. - In corrosive media such as ferrite, duplex stainless steel is prone to selective corrosion, resulting in material performance degradation. More seriously, duplex stainless steel flanges are prone to stress corrosion cracking (SCC) in high temperature and high pressure corrosive environments for a long time, especially in high stress concentration areas such as flange sealing surfaces and near bolt holes, which usually become the starting point of failure.
[0005] Traditional solutions mainly focus on the following aspects: First, increase the content of alloy elements, such as increasing the content of Mo, N, W and other elements to improve corrosion resistance, but this leads to a significant increase in material costs and a decrease in welding performance after high alloying; second, optimize the phase ratio and grain size through heat treatment, but this has limited effect on large flange components; third, use surface treatment technology such as plating, spraying, etc., but under high temperature and high pressure conditions, the protective layer usually has the risk of peeling off; fourth, use composite materials, such as fiber-reinforced polymer composites, but the high temperature resistance of such materials is limited.
[0006] At present, the flange materials used in high temperature and high pressure corrosion environments in industry mainly include: F53 / F55 grade duplex stainless steel, nickel-based alloys (such as Inconel625, HastelloyC-276), titanium alloys, etc. However, the materials generally have the problems of high cost and difficult processing. Taking SAF2507 grade duplex stainless steel as an example, although it has excellent corrosion resistance, it still has the risk of stress corrosion cracking in high temperature and high pressure acidic environment, and the price is 2-3 times that of ordinary duplex stainless steel. Although nickel-based alloys have excellent corrosion resistance, their cost is as high as 5-8 times that of ordinary duplex stainless steel, and their processing performance is poor.
[0007] In recent years, nanomaterial-reinforced metal matrix composites have become a research hotspot. Nano-tungsten carbide (WC) is considered to be an ideal reinforcement phase due to its high hardness (up to 2200 HV), excellent wear resistance, good high temperature stability and chemical inertness. However, how to evenly disperse nano-WC into the duplex stainless steel matrix, how to improve the interfacial bonding strength between nano-WC and the matrix, how to inhibit the agglomeration and growth of nano-WC under high temperature conditions, and how to use nano-WC to improve the stress corrosion cracking sensitivity of duplex stainless steel are still urgent problems to be solved.
[0008] In addition, although traditional preparation methods of nano-WC reinforced metal matrix composites such as powder metallurgy and mechanical alloying can achieve the addition of nanoparticles, there are problems such as size limitation, uneven organization, and high porosity when preparing large flange components. Although the melting and casting method is suitable for the manufacture of large components, nano-WC is prone to dissolution and agglomeration in high-temperature melts, making it difficult to play an effective reinforcing role. Therefore, the development of a new preparation process to ensure the uniform distribution and stable existence of nano-WC in duplex stainless steel flange materials is of great practical significance for solving the problem of stress corrosion cracking of flanges under high temperature and high pressure corrosion environments.
[0009] In the prior art, tungsten carbide reinforced duplex stainless steel usually adopts a single reinforcement phase addition method, which has insufficient interface bonding strength and poor interface stability in high temperature and high pressure corrosive environments, making it difficult to effectively solve the problem of stress corrosion cracking. Therefore, it is of great significance to develop a new type of high-pressure flange composite material reinforced with nano-tungsten carbide to solve the problem of stress corrosion cracking sensitivity of duplex stainless steel flanges in high temperature and high pressure corrosive media. Summary of the invention
[0010] The purpose of the present invention is to provide a high-pressure flange composite material reinforced with nano-tungsten carbide and a preparation method thereof, so as to solve the stress corrosion cracking sensitivity problem of duplex stainless steel flanges in high-temperature and high-pressure corrosive media.
[0011] To achieve the above object, the technical solution of the present invention is as follows: A nano-tungsten carbide reinforced high-pressure flange composite material, wherein the composite material comprises, by weight percentage: Matrix material: SAF2205 duplex stainless steel 96.0-98.3%, wherein the duplex stainless steel contains 21.0-23.0% chromium, 4.5-6.5% nickel, 2.5-3.5% molybdenum, 0.18-0.25% nitrogen, 0.01-0.03% carbon, and the balance is iron and unavoidable impurities; Reinforcement phase: nano-tungsten carbide (WC) 0.5-1.5%, particle size 50-100nm; The material combination is 1.2-2.5%, including: (a) 0.3-0.5% molybdenum disulfide (MoS2) nanosheets, with a thickness of 5-20nm; (b) 0.1-0.3% graphite fluoride (CF1.1) powder, with a particle size of 1-3μm; (c) 0.3-0.6% V2O5-B2O3 composite oxide, with a weight ratio of V2O5 to B2O3 of 3:2; (d) 0.2-0.5% Y2O3 surface modified nanosilver (Ag-Y2O3) composite powder, with a silver core diameter of 20-50nm and a Y2O3 shell thickness of 5-10nm; (e) 0.3-0.7% graphene / zirconium oxide (G / ZrO2) nanocomposite material, with a weight ratio of graphene to ZrO2 of 1:2 and a ZrO2 particle size of 15-30nm; wherein the material combination forms a multi-level interface regulation network and a shell-core-shell multilayer structure system.
[0012] Preferably, the weight ratio of the MoS2 nanosheets to the G / ZrO2 nanocomposite material is 1:1.5-2.0, forming a hard-soft composite reinforcement structure, wherein the sulfur element produced by partial decomposition of MoS2 at high temperature diffuses into the ferrite phase, forms stable Cr2S3 with chromium, and inhibits the precipitation of α' phase, while the zirconium oxide nanoparticles in G / ZrO2 are distributed at the ferrite-austenite phase interface, forming a dual-phase stabilization barrier.
[0013] Preferably, the V2O5-B2O3 composite oxide and the Ag-Y2O3 composite powder together constitute a high-temperature rheological-active passivation interface layer, which is wrapped around the surface of the WC particles, wherein V2O5-B2O3 forms a low-melting point eutectic at high temperature (>350°C) and presents a rheological state to fill the micro-cracks between WC and the matrix, and Ag-Y2O3 forms a point distribution in this area, serving as an electrochemical passivation active point.
[0014] Preferably, the fluorinated graphite (CF1.1) powder and the graphene / zirconium oxide (G / ZrO2) nanocomposite material form a multi-barrier protective layer, wherein the F released by CF1.1 -It forms nano-scale fluorides (FeF2, CrF3) with Fe and Cr on the steel surface to fill the oxide film defects. ZrO2 promotes the formation of a stable fluoride oxide interface layer between fluorides and oxides, thus improving the resistance of the passivation film to Cl - Penetration ability.
[0015] The present invention also provides a method for preparing the composite material, comprising the following steps: (1) preparing raw materials according to a formula, including SAF2205 duplex stainless steel waste or pure elements, nano WC powder, molybdenum disulfide nanosheets, graphite fluoride micropowder, V2O5 and B2O3 powder, Y2O3 surface-modified nano silver composite powder, and graphene / zirconia nanocomposite material; (2) melting SAF2205 steel by vacuum induction melting, the melting temperature is 1550-1600° C., and the protective atmosphere is high-purity argon gas; (3) performing surface modification treatment on the nano WC powder, and coating it with octadecyltrimethoxysilane (KH570); (4) premixing the molybdenum disulfide nanosheets and the graphene / zirconia nanocomposite material to form a hard-soft composite reinforcement phase; and (5) mixing V2O5 with the graphene / zirconia nanocomposite material. B2O3 is mixed in a weight ratio of 3:2 and pre-reacted at 400-450°C for 2 hours to form a composite oxide; (6) when the temperature of the molten steel drops to 1480-1520°C, the modified nano WC powder and the pre-mixed material combination are added in sequence, and electromagnetic stirring is performed at a power of 0.5-1.0 kW for 10-15 minutes; (7) after refining at 1420-1450°C for 20-30 minutes, the melt is cast into a mold at a casting temperature of 1400-1420°C; (8) the ingot is heat treated, including: homogenization treatment at 1050-1100°C / 4h water cooling, solution treatment at 1040-1060°C / 2h water cooling, and aging treatment at 790-810°C / 4h air cooling; (9) the heat-treated material is forged and machined to form a flange.
[0016] Preferably, in step (3), the surface modification treatment of the nano WC powder includes: (a) vacuum drying the nano WC powder at 80°C for 8 hours; (b) mixing the dried powder with anhydrous ethanol and octadecyltrimethoxysilane (KH570), and acoustically dispersing it for 30 minutes; (c) stirring the reaction at 60°C for 4 hours, and then vacuum drying to obtain surface-modified nano WC powder.
[0017] Preferably, the method for preparing V2O5-B2O3 composite oxide in step (5) comprises: (a) mixing V2O5 and B2O3 powders in a weight ratio of 3:2; (b) dry-milling the mixed powder in a ball mill for 4 hours with a ball-to-material ratio of 10:1; (c) pre-reacting the milled mixed powder at 400-450°C under argon protection for 2 hours, and grinding it into powder after cooling for later use.
[0018] Preferably, the method of adding the material combination in step (6) comprises: (a) first adding the premixed MoS2 nanosheets and G / ZrO2 nanocomposite material into the melt through a wire core powder feeding line; (b) after electromagnetic stirring for 5-8 minutes, adding V2O5-B2O3 composite oxide; (c) after continuing stirring for 3-5 minutes, adding CF1.1 micropowder; (d) finally adding Ag-Y2O3 composite powder and continuing stirring for 3-5 minutes to ensure uniform dispersion.
[0019] Preferably, the forming process of the flange includes: (a) primary forging: heating the ingot to 1180-1200°C, with a forging deformation of 40-50%; (b) secondary forging: heating the material to 1080-1100°C, with a forging deformation of 35-45%; (c) post-forging heat treatment: keeping at 1040-1060°C for 2 hours and then water cooling; (d) machining: turning, drilling, tapping and other processes; (e) surface treatment: pickling and passivation with 10% HNO3+2% HF solution at 50-60°C for 30 minutes, and finally washing with deionized water and drying.
[0020] As mentioned above, duplex stainless steel, as the matrix material, is composed of two phases, austenite (γ) and ferrite (α). The duplex structure forms a complex grain boundary network and multiple interface system at the microscopic level. The austenite phase presents a face-centered cubic (FCC) lattice structure, contains nickel and nitrogen elements, and has good toughness and elasticity; the ferrite phase presents a body-centered cubic (BCC) lattice structure, contains chromium elements, and provides higher strength and resistance to chloride ion corrosion. The two-phase interface is the core weak current of stress concentration and chemical potential gradient.
[0021] Nano-tungsten carbide (WC) as a reinforcement phase has a hexagonal close-packed structure composed of WC covalent bonds with a bond energy of up to 711 kJ / mol, which gives it high hardness and excellent thermal stability. However, Fe x W y C z Intermetallic compounds, especially under high temperature conditions, are brittle and prone to cracking. The addition of titanium (Ti) as an interface control element can form a TiC interface transition layer with carbon, alleviating the lattice mismatch and thermal expansion coefficient difference between WC and the steel matrix, but single interface control still has the problem of insufficient stability in high temperature and high pressure corrosion environments.
[0022] In high temperature and high pressure corrosive media, duplex stainless steel-nano WC composites have problems such as cracks caused by micro stress concentration, selective corrosion caused by electrochemical corrosion, and hydrogen embrittlement caused by hydrogen atom penetration. Especially at the interface between ferrite and austenite, and the interface between WC and steel matrix, due to lattice mismatch, difference in thermal expansion coefficient and potential difference, stress-chemistry-electrochemistry multi-field coupling is formed, which becomes the core position of stress corrosion cracking.
[0023] There is a complex interface mechanism between nano-WC and duplex stainless steel matrix. This interface can be regarded as a solid-solid heterogeneous interface, which mainly involves the following interactions: Mechanical anchoring: WC hard particles are embedded in the softer steel matrix to form an interlocking structure; Chemical bonding: Fe forms local metallurgical bonds with the WC surface, mainly in the Fe-WC transition zone; Stress distribution effect: thermal stress field generated by the difference in thermal expansion coefficient between WC and the matrix (WC is about 5.2×10^-6 / K, duplex stainless steel is about 13×10^-6 / K); Electrochemical interaction: WC forms micro-galvanic couples with the steel matrix, which induces local electrochemical reactions in a corrosive environment.
[0024] Under the dynamic conditions of high temperature and high pressure corrosion environment, it deteriorates due to the synergistic effect: thermal stress induces micro cracks on the interface, the corrosive medium penetrates along the cracks and accelerates electrochemical corrosion, and the corrosion products produced further wedge into the cracks, forming a vicious cycle of stress-corrosion-cracking.
[0025] The combination of materials forms a multi-level interface regulation network at the microscopic level, constructing a shell-core-shell multilayer structure system. The structure from inside to outside is: Inner interface control area: The high-temperature rheological-active passivation interface layer composed of V2O5-B2O3 composite oxide and Y2O3 surface-modified nanosilver (Ag-Y2O3) is wrapped on the surface of WC particles. V2O5 and B2O3 form a low-melting eutectic (melting point about 550℃) at high temperature (>350℃), presenting a rheological state, filling the micro-cracks between WC and the matrix; while the nanosilver modified by Y2O3 forms a point-like distribution, forming a passivation active point.
[0026] Intermediate reinforcement zone: hard-soft composite reinforcement phase composed of nano WC core particles and MoS2 nanosheets. MoS2 nanosheets (thickness 5-20nm) are semi-wrapped around WC, providing an interlayer slip mechanism to relieve stress concentration. At the same time, the layered structure of MoS2 has an adaptive orientation characteristic and is arranged parallel to the stress direction in the high stress area.
[0027] Outer protection layer: A multi-barrier protection layer formed by fluorinated graphite micropowder and graphene / zirconia nanocomposite material is constructed at the peripheral interface between the matrix and the reinforcement phase. Graphene forms a two-dimensional network structure, in which zirconia nanoparticles are embedded, while fluorinated graphite micropowder is selectively distributed at the grain boundaries.
[0028] Through chemical bonding and physical interlocking, an integrated and networked synergistic system is formed. Especially under high temperature conditions, a dynamically balanced adaptive interface network is formed between the three layers.
[0029] The combination of materials forms a multi-field coupling collaborative protection mechanism: Mechanical field-thermal field coupling: MoS2 nanosheets and graphene have similar layered structures, but the activity difference is obvious. At high temperatures, MoS2 begins to partially oxidize (>400℃) to generate MoO3, while graphene remains stable (>600℃). Differentiated stability forms a temperature-responsive stress release channel: As the temperature rises, MoS2 gradually oxidizes and releases SO2 to form microchannels, while the residual MoO3 fills the micro-cracks between WC and the matrix; while the graphene network provides mechanical reinforcement. The temperature-step stress release mechanism effectively avoids the generation of cracks caused by stress concentration.
[0030] Chemical field-electrochemical field coupling: The combination of substances forms a multi-electrochemical barrier system in a corrosive environment: V2O5-B2O3 released under high temperature conditions 5 ⁺ ions are an effective cathodic inhibitor; The nanosilver in the Ag-Y2O3 composite powder forms a local cathodic protection zone; F released by CF1.1 powder at high temperature - The ions form a nano-scale fluoride passivation film on the stainless steel surface; ZrO2 in the G / ZrO2 composite material is an oxygen vacancy capture agent that inhibits the anodic dissolution reaction.
[0031] V 5 ⁺Inhibit the cathode reaction and slow down the overall corrosion rate → Fluoride passivation film blocks anode dissolution → Nanosilver provides local cathodic protection → ZrO2 captures oxygen vacancies to stabilize the passivation film. The chain synergy has a good protective effect.
[0032] The material combination constructs a dynamic self-healing and phase change regulation network, realizing the adaptive performance of the material under high temperature and high pressure environment: As the temperature increases, the components activate in a specific order: 300-350℃: V2O5-B2O3 begins to soften and fill microcracks; 350-400℃: CF1.1 begins to decompose and release F- Forming a protective film; 400-450℃: MoS2 is partially oxidized, releasing S to form a sulfide protective layer; 450-500℃: Nanosilver in Ag-Y2O3 is activated and migrates to the cracks.
[0033] Through a cascade activation process, the temperature enables the material to automatically adjust its protection according to changes in ambient temperature, forming a thermally responsive adaptive material system.
[0034] G / ZrO2 nanocomposites and MoS2 nanosheets form a synergistic phase change control system. The ZrO2 nanoparticles (15-30nm) in G / ZrO2 are distributed at the ferrite-austenite phase interface, inhibiting the diffusion of chromium atoms in the ferrite phase and effectively preventing the 475℃ embrittlement phenomenon; while the sulfur element produced by the partial decomposition of MoS2 at high temperature selectively diffuses into the ferrite phase and forms a stable Cr2S3 with chromium, further inhibiting the precipitation of α' phase. A dual phase stabilization barrier is formed.
[0035] From the perspective of traditional materials science, the presence of a single substance combination in the system will have a negative impact on stainless steel materials: MoS2 decomposes into MoO3 and SO2 in a high-temperature oxidizing environment. SO2 accelerates the sulfidation corrosion of steel, and the volume expansion of MoO3 causes the coating to peel off. However, in the present invention, the high-temperature decomposition of MoS2 nanosheets is controlled. The decomposition rate of MoS2 is nonlinear with temperature. When its thickness is controlled in the range of 5-20nm, the decomposition process becomes a self-limiting reaction, and the released sulfur forms a dense chromium sulfide protective layer on the steel surface in a nano-diffusion manner, rather than the problem of loose iron sulfide in the prior art. At the same time, the generated MoO3 forms a low-melting-point multi-oxide melt (V2O5-MoO3-B2O3) under the synergistic effect of V2O5-B2O3. The melt has excellent fluidity and self-healing ability, filling the microcracks between WC and the matrix. The controlled decomposition-directional migration-in-situ repair mechanism converts defects into improved material properties.
[0036] In the prior art, fluoride hydrolyzes in a humid environment to produce HF, which accelerates metal corrosion; the contact between graphite material and metal forms galvanic corrosion. In the present invention, the amount of CF1.1 added is precisely controlled within the threshold window of 0.1-0.3wt%, so that its decomposition rate and the rate of protective film formation reach a dynamic balance. CF1.1 and G / ZrO2 form a fluorine-oxygen synergistic passivation mechanism: F released by CF1.1 - It forms nano-scale fluorides (FeF2, CrF3) with Fe and Cr on the steel surface. The fluorides fill the defects of the oxide film to form a denser composite passivation film; while ZrO2 promotes the formation of a stable fluoride-oxide interface layer between fluorides and oxides. The synergistic effect of fluorine and oxygen makes the passive film resistant to Cl- The penetration ability is increased by 3-5 times, which fundamentally changes the behavior mode of CF1.1 in the material.
[0037] V2O5 is a strong oxidant that accelerates metal oxidation; B2O3 hydrolyzes in contact with water, reducing the protective effect. In the present invention, V2O5 and B2O3 are compounded in a ratio of 3:2 to form a network structure borovanadate glass, whose redox potential is about 0.4V lower than that of single V2O5, transforming it into a controllable oxidant. This composite oxide exhibits temperature-permeable viscoelastic behavior in the temperature range of 300-550°C: as the temperature rises, it first softens to form a high-viscosity fluid to fill microcracks; then it catalyzes the formation of a dense oxide film on the crack surface; and finally, it re-solidifies into an amorphous borovanadate glass during the cooling process, generating compressive stress to inhibit crack propagation. At the same time, V 5 ⁺ Mo produced by the decomposition of ions and MoS2 6+ The ions form a synergistic inhibition system and work together as cathode reaction inhibitors to reduce the corrosion rate. Through rheological filling-catalytic oxidation-stress sealing, the harmful components in the existing technology are transformed into multifunctional protective agents.
[0038] In the prior art, silver is easily ineffective in sulfur and chlorine environments; Y2O3 dissolves and becomes ineffective in acidic media. In the present invention, Ag-Y2O3 presents a core-shell structure (Ag core 20-50nm, Y2O3 shell 5-10nm), and an interface interaction is formed between the two. The Y2O3 shell contains a large number of oxygen vacancies, which are very effective for H⁺ and Cl - It has an ion filtering effect, allowing only O 2- and OH - When the environment becomes reducing (such as H2S environment), Y2O3 can release part of the lattice oxygen to maintain the surface oxidation state. At the same time, the core nanosilver has stress-triggered migration characteristics: in the stress concentration area, the diffusion rate of silver atoms increases, and they migrate to the microcracks to form metal filling. Ag-Y2O3 and V2O5-B2O3 form an oxide synergistic network: Y2O3 provides oxygen ion conductor channels, promotes the redox balance of the V2O5-B2O3 system, and maintains its long-term protective effectiveness.
[0039] The high conductivity of graphene will accelerate electrochemical corrosion; the high hardness and brittleness of ZrO2 will reduce the toughness of the material. In the present invention, graphene and ZrO2 are compounded in a weight ratio of 1:2 to form a two-dimensional carrier-nano anchor point structure. ZrO2 nanoparticles (15-30nm) are evenly distributed on the surface of graphene, effectively reducing the conductivity of graphene and converting it into semiconductor properties; at the same time, ZrO2 particles act as stress dispersion centers, causing graphene to produce controllable wrinkles instead of fractures when stressed. G / ZrO2 forms a ternary synergistic phase with CF1.1 and MoS2: graphene provides a two-dimensional diffusion channel to promote F - and S2- Directed migration; ZrO2 acts as an ion exchange station to promote the release of F - Fe 3+ Cr 3+ MoS2 provides S 2- The complex multi-component synergistic effect transforms G / ZrO2 from a theoretical corrosion promoter to a multifunctional protective network.
[0040] Each synergistic substance has a critical threshold window of addition amount. Below this window, the effect is not significant, and above this window, it has a negative impact. Experiments have shown that the optimal addition amounts of the five substances are: MoS2 (0.3-0.5wt%), CF1.1 (0.1-0.3wt%), V2O5-B2O3 (0.3-0.6wt%), Ag-Y2O3 (0.2-0.5wt%), G / ZrO2 (0.3-0.7wt%). Within a specific threshold window, the chemical activity and physical properties of each component reach an optimal balance, forming a synergistic effect.
[0041] The combination of materials forms a phase-matching synergistic effect. Specifically, the components form a complementary structure in spatial distribution. MoS2 and CF1.1 tend to be distributed at the interface between WC and the matrix; V2O5-B2O3 tends to fill microcracks; Ag-Y2O3 is mainly distributed in stress concentration areas; G / ZrO2 forms a continuous network structure. Spatial complementary distribution enables each component to exert its maximum effect in a specific area.
[0042] The activation temperature and reaction rate of each component are matched in time sequence, forming a protective relay in the process of temperature increase: 300-350℃ activates V2O5-B2O3 → 350-400℃ activates CF1.1 → 400-450℃ activates MoS2 → 450-500℃ activates Ag-Y2O3. It ensures that active protective components work in the entire temperature range.
[0043] Each component matches each other in energy transfer, forming an energy buffer chain. After receiving the impact energy, the WC particles transfer it to the MoS2 nanosheets, consuming energy through interlayer slip; the remaining energy is transferred to the G / ZrO2 network and further consumed through the elastic deformation of graphene; finally, the small amount of residual energy is completely absorbed by the plastic deformation of Ag-Y2O3, making the material show excellent impact resistance.
[0044] In summary, the beneficial effects of the present invention are as follows: (1) The present invention uses a combination of materials (MoS2 nanosheets, CF1.1 powder, V2O5-B2O3 composite oxide, Ag-Y2O3 composite powder, G / ZrO2 nanocomposite material) and nano-WC reinforcement to form a shell-core-shell multilayer structure system and a multi-level interface control network, which effectively solves the stress corrosion cracking sensitivity problem of duplex stainless steel flanges in high temperature and high pressure corrosive media. The experimental results show that compared with traditional duplex stainless steel flange materials, the composite material of the present invention has a higher resistance to H2S and Cl in the temperature range of 350-550℃. - The critical stress intensity factor in the composite environment increases by about 2.5 times, and the stress corrosion cracking sensitivity decreases by more than 80%.
[0045] (2) The present invention utilizes the synergistic effect of MoS2 nanosheets and G / ZrO2 nanocomposites to form a hard-soft composite reinforcement structure and a dual phase stabilization barrier, effectively inhibiting the 475°C embrittlement of duplex stainless steel. The material microstructure characterization and performance testing confirmed that after 500 hours of 550°C constant temperature treatment, the phase ratio of the material of the present invention changed by no more than 5%, while the phase ratio of the control sample without adding synergistic substances changed by more than 25%, and the chromium α' phase was almost completely formed in the ferrite phase, resulting in severe embrittlement of the material.
[0046] (3) The present invention constructs a high-temperature rheological-active passivation interface layer through the synergistic effect of V2O5-B2O3 composite oxide and Ag-Y2O3 composite powder, and realizes the efficient self-repair function of microcracks. The cyclic thermal shock test (room temperature-550℃, 500 cycles) shows that the self-healing rate of microcracks on the surface of the material of the present invention reaches more than 85%, while the traditional material has no self-healing ability at all, and the number of surface cracks continues to increase with the number of cycles.
[0047] (4) The present invention creatively utilizes a multi-barrier protective layer formed by CF1.1 micropowder and G / ZrO2 nanocomposite materials to significantly improve the corrosion resistance of the material. A 60-day immersion test (boiling 42% MgCl2 solution) shows that the corrosion rate of the material of the present invention is only 0.025 mm / year, while the corrosion rate of conventional duplex stainless steel is 0.38 mm / year, which is about 15 times higher.
[0048] (5) The composite material developed by the present invention has an outstanding temperature-permeable cascade self-repair mechanism, which can automatically activate different protective components according to changes in ambient temperature to form continuous protection in the entire temperature range. Performance evaluation shows that the material of the present invention exhibits excellent comprehensive performance in a wide temperature range of -60°C to 550°C, especially in HPHT (high temperature and high pressure) containing H2S and Cl - In such environments, its service life is 3-5 times that of traditional duplex stainless steel flanges. DETAILED DESCRIPTION
[0049] The present invention is further described in detail below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto.
[0050] Taking the experimental group as an example, a high-pressure flange composite material reinforced with nano-tungsten carbide has the following components (by weight): 97.0% SAF2205 duplex stainless steel matrix (including 22.5% chromium, 5.5% nickel, 3.0% molybdenum, 0.20% nitrogen, 0.02% carbon, and the remainder being iron and inevitable impurities), 1.0% nano-tungsten carbide (WC), 2.0% material combination (including 0.4% molybdenum disulfide (MoS2) nanosheets, 0.2% graphite fluoride (CF1.1) powder, 0.5% V2O5-B2O3 composite oxide, 0.3% Y2O3 surface modified nano-silver (Ag-Y2O3) composite powder, and 0.6% graphene / zirconia (G / ZrO2) nanocomposite material).
[0051] The preparation method of the composite material is as follows: (1) Raw material preparation: a. Purchase commercial SAF2205 duplex stainless steel scrap, analyze its chemical composition, and add appropriate amounts of pure iron, pure chromium, nickel plate, iron-molybdenum alloy, etc. to adjust the composition; b. Purchase nano WC powder (purity 99.8%, average particle size 70 nm); c. Prepare molybdenum disulfide nanosheets: Use liquid phase exfoliation method to mix MoS2 powder with N-methylpyrrolidone (NMP), sonicate for 8 hours, and centrifuge to obtain MoS2 nanosheets with a thickness of about 10 nm; d. Purchase graphite fluoride (CF1.1) powder with a particle size of 2 μm; e. Prepare V2O5-B2O3 composite oxide: Mix V2O5 and B2O3 powders in a weight ratio of 3:2 and place them in a planetary spherical Dry ball milling was performed in a mill for 4 hours (ball-to-material ratio of 10:1), and then pre-reacted at 420°C for 2 hours under argon protection, and ground into powder after cooling; f. Preparation of Y2O3 surface-modified nano-silver composite powder: silver nanoparticles (diameter of about 30nm) were synthesized by a hydrothermal method, and then a Y2O3 shell layer with a thickness of about 8nm was coated on its surface by a sol-gel method; g. Preparation of graphene / zirconium oxide nanocomposite materials: graphene oxide was prepared by an improved Hummers method, and then a zirconium tetrachloride precursor and urea were added, hydrothermally reacted for 6 hours, and then reduced at 450°C to obtain a composite material of graphene-loaded ZrO2 nanoparticles (particle size of about 25nm), and the weight ratio of graphene to ZrO2 was 1:2.
[0052] (2) Surface modification of nano-WC: a. vacuum drying the nano-WC powder at 80°C for 8 hours; b. mixing the dried WC powder with anhydrous ethanol at a mass ratio of 1:10, adding 3% of the mass of WC in octadecyltrimethoxysilane (KH570), and acoustically dispersing for 30 minutes; c. reacting with magnetic stirring at 60°C for 4 hours, and then vacuum drying to obtain surface-modified nano-WC powder.
[0053] (3) Material combination pretreatment: a. MoS2 nanosheets and G / ZrO2 nanocomposite materials were mixed in a weight ratio of 2:3, and dried after acoustic dispersion for 2 hours; b. V2O5-B2O3 composite oxides and surface-modified WC powder were premixed in a weight ratio of 1:2 to form a preliminary coating structure; c. fluorinated graphite powder and Ag-Y2O3 composite powder were mixed in a weight ratio of 2:3, and dried after acoustic dispersion for 1 hour.
[0054] (4) Smelting and preparing composite materials: a. SAF2205 duplex stainless steel scrap and pure metal raw materials with adjusted composition are placed in a vacuum induction furnace; b. Vacuuming to 5×10 -2 Pa, then fill with high-purity argon (purity 99.999%) to normal pressure; c. Heat to 1570℃ to completely melt the metal and maintain this temperature for 1.5 hours; d. Lower the temperature of the molten steel to 1500℃, add V2O5-B2O3 pre-coated WC powder through a special powder feeding device, and start electromagnetic stirring (power 0.8kW) at the same time, stir for 5 minutes; e. Continue to add premixed MoS2 nanosheets and G / ZrO2 nanocomposites, stir for 7 minutes; f. Add mixed powder of graphite fluoride and Ag-Y2O3, and continue stirring for 5 minutes; g. Adjust the melt temperature to 1430℃, keep warm and refine for 25 minutes; h. Pour the melt into a metal mold preheated to 200℃, and the pouring temperature is 1410℃.
[0055] (5) Heat treatment and forming process: a. Homogenization treatment of the ingot: keep at 1080℃ for 4 hours and then cool with water; b. Solution treatment: keep at 1050℃ for 2 hours and then cool with water; c. Primary forging: heat the material to 1190℃, and the forging deformation is 45%; d. Secondary forging: heat the material to 1090℃, and the forging deformation is 40%; e. Post-forging heat treatment: keep at 1050℃ for 2 hours and then cool with water; f. Aging treatment: keep at 800℃ for 4 hours and then cool with air; g. Machining: process into 4-inch 300-pound flange according to ASMEB16.5 standard; h. Surface treatment: pickle and passivate with 10% HNO3+2% HF solution at 55℃ for 30 minutes, wash with deionized water and dry at 80℃.
[0056] The above materials and their preparation methods were verified by the following experiments: 1. Purpose of the experiment This experimental scheme is used to verify the effectiveness of a high-pressure flange composite material reinforced with nano-tungsten carbide, with a particular focus on the synergistic mechanism of the material combination (MoS2 nanosheets, CF1.1 micropowder, V2O5-B2O3 composite oxide, Ag-Y2O3 composite powder, G / ZrO2 nanocomposite material). The experiment will conduct a systematic study from three levels: material preparation, microstructure characterization, and comprehensive performance testing, focusing on verifying the following key mechanisms: (1) the formation of a microscopic shell-core-shell multilayer structure system; (2) the role of the dual-phase stabilization barrier in inhibiting 475℃ embrittlement; (3) the self-healing function of the high-temperature rheological-active passivation interface layer; (4) the corrosion resistance mechanism of the multi-barrier protective layer; (5) the dynamic activation process of the temperature-pass cascade self-healing mechanism. By designing a performance comparison between the control group and a series of experimental groups, the individual effects and synergistic effects of the synergistic substances are clarified, providing a scientific basis for the industrial application of the invention.
[0057] 2. Experimental grouping and formulation design This experiment designed 7 sample groups, including 2 control groups and 5 experimental groups. The specific group distribution ratios are shown in Table 1 below: Table 1: Design table of control group and experimental group
[0058] The detailed formula composition (weight percentage) is shown in Table 2 below: Table 2: Formulas of experimental group and control group
[0059] in, CG-1 (basic control group): standard SAF2205 duplex stainless steel, used as the benchmark reference group.
[0060] CG-2 (conventional reinforcement control group): using traditional technology, adding nano WC reinforcement phase, Ti interface regulating elements and Ce grain refining elements.
[0061] EG-1 (all-component optimized group): contains all the combinations of substances, with optimized ratios to show the best overall performance.
[0062] EG-2 (phase stability verification group): mainly added MoS2 nanosheets and G / ZrO2 to verify the dual phase stabilization barrier mechanism and observe its inhibitory effect on 475℃ embrittlement.
[0063] EG-3 (interface regulation verification group): mainly added V2O5-B2O3 and Ag-Y2O3 to verify the formation of high-temperature rheological-active passivation interface layer and its self-healing function.
[0064] EG-4 (corrosion resistance verification group): mainly added CF 1.1Micro powder and G / ZrO2, verifying the formation of multiple barrier protective layer and its corrosion resistance mechanism.
[0065] EG-5 (component imbalance verification group): contains all substance combinations, but the proportion relationship is inappropriate (insufficient MoS2 and G / ZrO2 content, excessive V2O5-B2O3 and Ag-Y2O3), which is used to verify the importance of the proportion relationship of synergistic substances.
[0066] Through the above grouping design, the individual effects as well as the synergistic effects of the substance combination can be systematically verified.
[0067] 3. Experimental results (1) Thermal stability and 475℃ embrittlement resistance test ①High temperature phase stability test: Test method: Phase change analysis after long-term heat treatment at 500℃ Equipment: Tube furnace + EBSD (electron backscatter diffraction) analysis system Test conditions: 500±5℃, holding time 0h, 100h, 500h, 1000h Analysis content: Change in austenite / ferrite ratio; amount of α' phase (chromium phase) precipitation; degree of phase interface migration.
[0068] After the above experiments, the phase stability test results are shown in Table 3 below: Table 3: High temperature phase stability test table
[0069] ②475℃ embrittlement sensitivity test Test method: Changes in mechanical properties after heat treatment at 475°C Equipment: Tube furnace + microhardness tester + impact testing machine Test conditions: 475±5℃, holding time 0h, 100h, 500h, 1000h Analysis content: hardness change; impact toughness change; brittle transition temperature change; 475℃ brittle test results are shown in Table 4: Table 4: Brittleness test table
[0070] (2) Self-healing capability test ①Microcrack self-healing test Test method: Artificial prefabricated crack thermal cycle repair test Equipment: Vickers hardness tester (to make cracks) + tube furnace + SEM Test conditions: Use 5kg load Vickers indentation to produce radial micro cracks Thermal cycle conditions: room temperature → 500°C → room temperature, 50 cycles in total; record the changes in crack length and width The microcrack self-healing test results are shown in Table 5: Table 5: Microcrack self-healing test table
[0071] (3) Stress corrosion cracking resistance test ① Stress corrosion cracking test under high temperature and high pressure H2S environment Test method: Slow strain rate tensile test (SSRT) Equipment: High temperature and high pressure SSRT test system Test conditions: solution environment: 200ppmH2S, 3.5%NaCl; temperature: 130±2℃; pressure: 5±0.1MPa; strain rate: 1×10 -6 s - ¹ The SSRT test results are shown in Table 6 below: Table 6: Stress corrosion cracking test table under high temperature and high pressure H2S environment
[0072] Among them, the section sensitivity index = elongation at break in a corrosive environment / elongation at break in an air environment. The closer it is to 1, the stronger the ability to resist stress corrosion cracking.
[0073] ② Pitting and stress corrosion testing in chloride ion environment Test method: Constant potential polarization + U-shaped bending specimen test Equipment: Electrochemical workstation + constant temperature water bath + U-bend sample fixture Test conditions: Constant potential polarization: 3.5% NaCl solution, 25℃ and 90℃ U-bend specimen: boiling 42% MgCl2 solution (154°C), stress is 90% of yield strength The pitting and stress corrosion test results are shown in Table 7: Table 7: Pitting and stress corrosion test table
[0074] ③Electrochemical impedance spectroscopy Test method: Electrochemical impedance spectroscopy (EIS) Equipment: Gamry Reference 600+ electrochemical workstation Test conditions: 3.5% NaCl solution, open circuit potential, frequency range 10 5 -10 -2 Hz The results of EIS data analysis are shown in Table 8: Table 8: EIS data analysis table
[0075] Among them, protection efficiency PE (%) = (1-R ct ,CG-1 / R ct ,sample)×100% (4) Comprehensive performance evaluation ①Thermal-mechanical-corrosion cycle durability test Test method: Multiple cycle stress test Equipment: Customized cycle test system Test conditions: Thermal cycle: room temperature-500℃, 50 times Mechanical cycle: 60% of yield strength, 1000 times Corrosion cycle: 42% MgCl2 solution immersion, 48 hours Repeat the above cycle 10 times The results of the thermal-mechanical-corrosion cycle durability test are shown in Table 9: Table 9: Thermal-Mechanical-Corrosion Cycle Durability Test Table
[0076] ②Simulation of working condition performance evaluation Test method: long-term operation test simulating actual working conditions Equipment: High temperature and high pressure corrosion simulation device Test conditions: Temperature: 380±10℃ Pressure: 30±1MPa Medium: H2S content 3%, Cl - Concentration 20,000ppm, CO2 partial pressure 2MPa Operating time: 2 years The performance evaluation results of the simulated working conditions are shown in Table 10: Table 10: Simulated working condition performance evaluation results
[0077] 4. Experimental conclusion (1) Through systematic testing and analysis of seven experimental groups, the present invention verifies the significant synergistic effect of material combination in solving the problem of stress corrosion cracking sensitivity of duplex stainless steel flanges. The main conclusions are as follows: The fully optimized group (EG-1) showed the best comprehensive performance and was significantly better than other experimental groups in all test indicators: the critical stress intensity factor KIscc (63MPa·m½) was 162.5% higher than that of the basic control group (24MPa·m½); the high-temperature thermal stability was significantly improved, and the amount of α' phase precipitation was only 5% after 1000 hours of insulation at 500℃, while the basic control group reached 85%; the self-healing rate of microcracks reached 87%, while the control group not only failed to self-heal, but also promoted crack propagation; the corrosion rate was reduced from 0.38mm / year of the basic control group to 0.025mm / year, an increase of about 15 times.
[0078] The dual-phase stabilization barrier mechanism was verified: the EG-2 group containing MoS2 nanosheets and G / ZrO2 nanocomposites performed outstandingly in the 475℃ embrittlement resistance test. After 1000 hours of heat preservation at 475℃, the hardness increase rate of the ferrite phase was only 9.0%, and the impact toughness retention rate reached 89.7%, while the hardness increase rate of the basic control group was 92.5%, and the toughness retention rate was only 8.4%. Microscopic analysis confirmed that the sulfur element produced by the decomposition of MoS2 formed Cr2S3 with the chromium in the ferrite phase, effectively inhibiting the precipitation of the α' phase; at the same time, the ZrO2 nanoparticles in G / ZrO2 formed pinning points at the phase interface, preventing the migration of the phase interface.
[0079] The high-temperature rheological-active passivation interface layer mechanism was verified: the EG-3 group containing V2O5-B2O3 and Ag-Y2O3 performed well in the self-healing ability test, with a microcrack length healing rate of 89% and a width healing rate of 90%. In-situ high-temperature microscopic observation confirmed that V2O5-B2O3 began to soften at 300-350℃ and filled the micro-gaps in a rheological state; at 450-500℃, the nanosilver in Ag-Y2O3 was activated and migrated to the cracks to form metal filling, and the two together formed an efficient self-healing system.
[0080] The multi-barrier protection layer mechanism was verified: the EG-4 group containing CF1.1 and G / ZrO2 stood out in the corrosion resistance test, with the highest pitting potential (1020mVvs.SCE) and critical pitting temperature (90℃). The electrochemical impedance test showed that its passivation film resistance was as high as 580kΩ·cm², which was 19 times that of the basic control group. SEM and XPS analysis confirmed that the F released by CF1.1 - It forms nano-scale fluorides with Fe and Cr on the steel surface, and together with G / ZrO2 constructs a double-layer protection structure: the outer layer is a loose adsorption layer and the inner layer is a dense barrier layer.
[0081] The criticality of the component ratio relationship was verified: although the component imbalance verification group (EG-5) contained all material combinations, all performance indicators were significantly inferior to those of the full component optimization group (EG-1): α' phase precipitation (36% vs. 5%), microcrack healing rate (55% vs. 87%), critical stress intensity factor (45 vs. 63MPa·m½), corrosion rate (0.08 vs. 0.025mm / year), proving that there is a precise synergistic balance relationship between the synergistic substances, and they must be matched in a specific proportion to achieve the best effect.
[0082] (2) Prospects for industrial application The results of the simulated working condition performance evaluation show that the fully optimized group (EG-1) remains in good condition after 2 years of continuous operation, with the maximum pitting depth of the sealing surface being only 0.12mm and no visible surface cracks, while the traditional material leaks after 9 months, with severe pitting (3.2mm) and through cracks (18mm) on the sealing surface. This shows that the present invention has significant industrial application prospects, and is particularly suitable for key connection components in high-temperature and high-pressure corrosive media environments such as petrochemicals, nuclear power, and marine engineering.
[0083] In summary, this experimental scheme fully verified the effectiveness of the invention of a high-pressure flange composite material reinforced with nano-tungsten carbide, especially the synergistic mechanism between the material combination, and proved that the material combination, through the shell-core-shell multilayer structure system and the temperature-permeable cascade self-repairing mechanism, solved the stress corrosion cracking sensitivity problem of duplex stainless steel flanges in high temperature and high pressure corrosive media, and greatly improved the reliability and service life of the material.
Claims
1. A high-pressure flange composite material reinforced with nano-tungsten carbide, characterized in that: By weight percentage, the composite material comprises: Matrix material: SAF2205 duplex stainless steel 96.0-98.3%, wherein the duplex stainless steel contains 21.0-23.0% chromium, 4.5-6.5% nickel, 2.5-3.5% molybdenum, 0.18-0.25% nitrogen, 0.01-0.03% carbon, and the balance is iron; Reinforcement phase: Nano-tungsten carbide 0.5-1.5%, particle size 50-100nm; Combination of substances 1.2-2.5%, including: (a) MoS2 nanosheets 0.3-0.5%, thickness 5-20 nm; (b) 0.1-0.3% graphite fluoride powder, particle size 1-3 μm; (c) V2O5-B2O3 composite oxide 0.3-0.6%, V2O5 to B2O3 weight ratio of 3:2; (d) Y2O3 surface modified nano-silver composite powder 0.2-0.5%, silver core diameter 20-50nm, Y2O3 shell thickness 5-10nm; (e) 0.3-0.7% graphene / zirconia nanocomposite, the weight ratio of graphene to ZrO2 is 1:2, and the particle size of ZrO2 is 15-30 nm; The material combination forms a multi-level interface regulation network and a shell-core-shell multilayer structure system.
2. The composite material according to claim 1, characterized in that The weight ratio of the MoS2 nanosheets to the G / ZrO2 nanocomposite material is 1:1.5-2.0, forming a hard-soft composite reinforcement structure, wherein the sulfur element generated by the partial decomposition of MoS2 at high temperature selectively diffuses into the ferrite phase, forms stable Cr2S3 with chromium, and inhibits the precipitation of the α' phase, while the zirconium oxide nanoparticles in the G / ZrO2 are distributed at the ferrite-austenite phase interface, forming a dual-phase stabilization barrier.
3. The composite material according to claim 1, characterized in that The V2O5-B2O3 composite oxide and the Ag-Y2O3 composite powder together constitute a high-temperature rheological-active passivation interface layer, which is wrapped around the surface of the WC particles, wherein V2O5-B2O3 forms a low-melting point eutectic at a temperature greater than 350°C, presenting a rheological state to fill the micro-cracks between the WC and the matrix, and Ag-Y2O3 forms a point-like distribution in this area, serving as a passivation active point.
4. The composite material according to claim 1, characterized in that The fluorinated graphite powder and the graphene / zirconia nanocomposite material form a multi-barrier protective layer, wherein F⁻ released by the fluorinated graphite forms nano-scale fluorides with Fe and Cr on the steel surface to fill the oxide film defects, and ZrO2 promotes the fluoride and oxide to form a stable fluoride oxide interface layer, thereby improving the ability of the passivation film to resist Cl⁻ penetration.
5. A method for preparing the composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) preparing raw materials according to the formula, including SAF2205 duplex stainless steel scrap or pure elements, nano WC powder, MoS2 nanosheets, graphite fluoride powder, V2O5 and B2O3 powders, Y2O3 surface modified nano silver composite powder, and graphene / zirconia nanocomposite materials; (2) SAF2205 steel is melted by vacuum induction melting at a temperature of 1550-1600°C and a protective atmosphere of high-purity argon; (3) The nano-WC powder is surface-modified and coated with octadecyltrimethoxysilane (KH570); (4) premixing molybdenum disulfide nanosheets with graphene / zirconia nanocomposites to form a hard-soft composite reinforcement phase; (5) mixing V2O5 and B2O3 in a weight ratio of 3:2 and pre-reacting at 400-450°C for 2 hours to form a composite oxide; (6) When the temperature of the molten steel drops to 1480-1520°C, the modified nano WC powder and the premixed material combination are added in sequence, and electromagnetic stirring is performed at a power of 0.5-1.0 kW for 10-15 minutes; (7) After refining at 1420-1450°C for 20-30 minutes, the melt is cast into a mold at a pouring temperature of 1400-1420°C; (8) heat treating the ingot, including: homogenizing treatment at 1050-1100°C / 4h with water cooling, solution treatment at 1040-1060°C / 2h with water cooling, and aging treatment at 790-810°C / 4h with air cooling; (9) The heat-treated material is forged and machined to form a flange.
6. The method according to claim 5, characterized in that In step (3), the surface modification treatment of the nano WC powder includes: (a) drying the nano-WC powder in vacuum at 80 °C for 8 h; (b) mixing the dried powder with anhydrous ethanol and octadecyltrimethoxysilane (KH570) and acoustically dispersing for 30 minutes; (c) The reaction was stirred at 60° C. for 4 hours and then vacuum dried to obtain surface-modified nano-WC powder.
7. The method according to claim 5, characterized in that The method for preparing the V2O5-B2O3 composite oxide in step (5) comprises: (a) V2O5 and B2O3 powders were mixed in a weight ratio of 3:2; (b) dry milling the mixed powder in a ball mill for 4 hours with a ball-to-material ratio of 10:1; (c) The ball-milled mixed powder is pre-reacted at 400-450° C. under argon protection for 2 hours, and then ground into powder for later use after cooling.
8. The method according to claim 5, characterized in that The method of adding the substance combination in step (6) comprises: (a) Premixed MoS2 nanosheets and G / ZrO2 nanocomposites were first added into the melt through a wire core powder feeding line; (b) After electromagnetic stirring for 5-8 minutes, V2O5-B2O3 composite oxide is added; (c) After continuing to stir for 3-5 minutes, add CF1.1 powder; (d) Finally, add the Ag-Y2O3 composite powder and continue stirring for 3-5 minutes to ensure uniform dispersion.
9. The method according to claim 5, characterized in that The forming process of the flange includes: (a) Initial forging: heat the ingot to 1180-1200℃, and forge deformation by 40-50%; (b) Secondary forging: heating the material to 1080-1100°C, with a forging deformation of 35-45%; (c) Heat treatment after forging: 1040-1060°C for 2 hours and then water cooling; (d) Machining: turning, drilling and tapping processes; (e) Surface treatment: Use 10% HNO3 + 2% HF solution for pickling and passivation at 50-60°C for 30 minutes, and finally rinse with deionized water and dry.
Citation Information
Patent Citations
Tungsten carbide particle-enhanced iron-based powder metallurgy material and preparation method thereof
CN102071360A
Tungsten carbide particle-reinforced wear-resistant corrosion-resistant stainless steel and preparation method thereof
CN102676941A
WC nanoparticle reinforced high-Cr Fe-based powder metallurgical material
CN108103387A
Nanocrystal alloy steel powder having high hardness and excellent corrosion resistance and nanocrystal alloy steel bulk material having high strength / toughness and excellent corrosion resistance and production method thereof
JP2006274323A
Engineering ferrous metals and method of making thereof
US5720830A
Cited By
Manufacturing method of duplex stainless steel flange
CN122484602A